Application and prospect of trabecular bone score in differentiated thyroid cancer patients receiving thyrotropin suppression therapy - Ran, Bingyu; Wei, Feng; Gong, Jian; Xu, Hao (Frontiers in Endocrinology, 2022)
Thyroid-stimulating hormone (TSH) suppression therapy is one of the common treatments for most patients with differentiated thyroid cancer (DTC). Unfortunately, its detrimental effects on bone health are receiving increasing attention. It may increase the risk of osteoporosis and osteoporotic fractures. The trabecular bone score (TBS) is a relatively new gray-scale texture measurement parameter that reflects bone microarchitecture and bone strength and has been shown to independently predict fracture risk. We reviewed for the first time the scientific literature on the use of TBS in DTC patients on TSH suppression therapy and aim to analyze and compare the utility of TBS with bone mass strength (BMD) in the management of skeletal health and prediction of fracture risk. We screened a total of seven relevant publications, four of which were for postmenopausal female patients and three for all female patients. Overall, postmenopausal female patients with DTC had lower TBS and a significant reduction in TBS after receiving TSH suppression therapy, but their BMD did not appear to change significantly. In addition, TBS was also found to be an independent predictor of osteoporotic fracture risk in postmenopausal women with DTC receiving TSH suppression therapy. However, due to limitations in the number of studies and study populations, this evidence is not sufficient to fully demonstrate the adverse effects of TSH suppression therapy on patients' TBS or BMD and the efficacy of TBS, and subsequent larger and more case-cohort studies are needed to further investigate the relationship and application of TBS to TSH suppression therapy in terms of skeletal health impairment and fracture risk in DTC patients.